Alguém pode me ajudar...???
Anexos:
![](https://pt-static.z-dn.net/files/d8f/2988dc433af79f0911a5c9fc49a5a971.jpg)
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo-a-passo:
Basta substituir o x pelos valores dados:
3 x² - 4 x + 1 Par ordenado
f(0) = 3(0)² - 4(0) + 1 = 3.0 - 0 + 1 = 0 - 0 + 1 = 1 (0,1)
f(-1) = 3(-1)² - 4.(-1) + 1 = 3.1 + 4 + 1 = 3 + 4 + 1 = 8 (-1,8)
f(4) = 3(4)² - 4.(4) + 1 = 3.16 - 16 + 1 = 48 - 15 = 33 (4,33)
f(-5) = 3(-5)² - 4.(-5) + 1 = 3.25 + 20 + 1 = 75 - 21 = 54 (-5,54)
f(8) = 3(8)² - 4.(8) + 1 = 3.64 - 32 + 1 = 192 - 31 = 161 (8,161)
Perguntas interessantes
Ed. Física,
10 meses atrás
Administração,
10 meses atrás
História,
10 meses atrás
Química,
1 ano atrás
Química,
1 ano atrás
Português,
1 ano atrás
História,
1 ano atrás